A CHALLENGE TOWARDS SUSTAINABLE FASHION CONSUMPTION: FAST FASHION AND IMPULSIVE PURCHASE BEHAVIOUR - Nurhidayah Rosely; Sharifah Faridah Syed Ali (International Journal of Accounting, Finance and Business, 2023)
The issue of overproduction and overconsumption of fashion goods has become critical since both manufacturers and consumers feel that the purchase and consumption of such goods do not create any harmful effects on society or the economy's well-being. Consumer demand has been a leading cause of the mushrooming fast fashion market; thus, this unsustainable consumption poses the greatest challenge for the government in promoting the green economy and achieving one of the sustainable development goals, responsible consumption practices. The theory of cognitive dissonance (Festinger, 1962) foregrounds the fact that consumers have inner needs and are capable of altering their cognition to seek consistency between attitudes and behaviours. Consumers are motivated to minimise the discrepancy between cognition and discomfort through several rationalisation strategies to justify their impulsive, excessive, and overconsumption of fast fashion goods. This review paper is intended to explore the role of social media, impulsive purchase behaviour, and cognitive dissonance in fast fashion consumption. Following the literature review, consumers’ involvement in fast fashion consumption is driven by social motivation. Although consumers are aware of the nature of fashion goods, which are easily faded and have a short life cycle that promote continuous purchase, which leads to waste and overconsumption, the role of social media and social factors motivate consumers towards impulsive purchase behaviour on fast fashion goods. This conceptual paper provided a basis to further explore consumers’ cognitive and affective states in order to rationalise their excessive consumption patterns, which could impede sustainable fashion consumption practices.